TRUST, SATISFACTION, AND LOYALTY OF ISLAMIC BANK CUSTOMERS: ROLE OF RELIGIOSITY - Wijaya, Evelyn; Junaedi, Achmad Tavip; Fransisca, Luciana; Chandra, Stefani; Suyono, Suyono (Universitas Brawijaya, Indonesia, 2023)
As one of the largest Muslim countries in the world, Indonesia has an important role in building a Sharia economy. The initial effort that can be made is to strengthen Sharia-based financial services. Currently, several Sharia-based banks are operating in Indonesia. However, the presence of Islamic banking has not been optimal in attracting customers to conduct financial transactions through Islamic banks. One of which is not optimal banking in applying the principle of religiosity in financial transactions. This research aimed to analyze the effect of religiosity on the trust, satisfaction, and loyalty of Islamic bank customers. The research population was all customers of Islamic banks in Pekanbaru City. An accidental sampling technique was used to get the sample of 220 respondents. Data analysis was done using path analysis with the help of the AMOS SEM program. The study's results stated that religiosity has a significant effect on customer trust and loyalty but is not significant on customer satisfaction. Customer trust has a significant effect on customer satisfaction. Customer satisfaction has no significant effect on customer loyalty. Therefore, Islamic banking must introduce and offer Sharia-based financial products to build loyal customers banks. Banks should continue to uphold Islamic teachings in every development of banking products and services to increase the trust, satisfaction, and loyalty of Islamic bank customers. In addition, banks need to retain customers who are already loyal to banks, considering that banking loyalty cannot be formed in a short timeThis research indicates that customer trust and loyalty can be formed if Islamic banks appropriately apply the principles of religious teaching in accordance with Islamic Sharia.